Electron Correlation in New Materials and Nanosystems - Scharnberg, Kurt.; Kruchinin, Sergei; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
The articles collected in this book cover a wide range of materials with extraordinary superconducting and magnetic properties. For many of the materials studied, strong electronic correlations provide a link between these two phenomena which were long thought to be highly antagonistic. Both the progress in our understanding of fundamental physical processes and the advances made towards the development of devices are reported here. The materials studied come in a variety of forms and shapes from bulk to epitaxial films, nano- and heterostructures down to those involving single molecules and double quantum dots. In some cases the structuring serves the study of bulk properties. More often it is the change of these properties with nanostructuring and the properties of different materials in close proximity with each other that are of key interest because of possible application of these materials or heterostructures to quantum computing and spintronics.
Quantum Nanodevices -- TRANSPORT PROPERTIES OF FULLERENE NANODEVICES -- NANOSCALE STUDIES ON METAL-ORGANIC INTERFACES -- ELECTRON-ELECTRON INTERACTION IN CARBON NANOSTRUCTURES -- SINGLE-LEVEL MOLECULAR RECTIFIER -- MAGNETIC UNIPOLAR FEATURES IN CONDUCTIVITY OF POINT CONTACTS BETWEEN NORMAL AND FERROMAGNETIC D-METALS (CO, NI, FE) -- Superconductivity -- II.1 Magnesium diboride and the two-band scenario -- II.1 Magnesium diboride and the two-band scenario -- II.1 Magnesium diboride and the two-band scenario -- II.1 Magnesium diboride and the two-band scenario -- II.1 Magnesium diboride and the two-band scenario -- II.1 Magnesium diboride and the two-band scenario -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- II.2 Cuprate and other unconventional superconductors -- Spintronics -- KONDO EFFECT IN MESOSCOPIC SYSTEM -- 1/f NOISE AND TWO-LEVEL SYSTEMS IN JOSEPHSON QUBITS -- SINGLE-ELECTRON PUMP: DEVICE CHARACTERIZATION AND LINEAR-RESPONSE MEASUREMENTS -- ZERO-BIAS CONDUCTANCE THROUGH SIDE-COUPLED DOUBLE QUANTUM DOTS -- SPIN-ORBITAL ORDERING AND GIANT MAGNETORESISTANCE IN COBALT OXIDES: INTRINSIC MAGNETIC-FIELD-EFFECT TRANSISTOR -- FERRIMAGNETIC DOUBLE PEROVSKITES AS SPINTRONIC MATERIALS* -- A POSSIBLE MODEL FOR HIGH-TC FERROMAGNETISM IN GALLIUM MANGANESE NITRIDES BASED ON RESONATION PROPERTIES OF IMPURITIES IN SEMICONDUCTORS -- LARGE MAGNETORESISTANCE EFFECTS IN NOVEL LAYERED RARE EARTH HALIDES.
Keywords: PHYSICS; QUANTUM COMPUTING; PARTICLES (NUCLEAR PHYSICS).; SUPERCONDUCTIVITY; MAGNETISM; NANOTECHNOLOGY; PHYSICS; SUPERCONDUCTIVITY, SUPERFLUIDITY, QUANTUM FLUIDS; MAGNETISM, MAGNETIC MATERIALS; NANOTECHNOLOGY; QUANTUM COMPUTING, INFORMATION AND PHYSICS; SOLID STATE PHYSICS AND SPECTROSCOPY